Threshold-free method for determining the composition of a two-phase composite from an microscopy images - Krasikova, I.E.; Krasikov, I.V.; Kuprin, V.V.; Vasiliev, O.O. (Physics and Chemistry of Solid State, 2025)
A new method is proposed for estimating the quantitative analysis of the composition of two-component composites from an image. This method does not rely on a binarization threshold and offers greater accuracy compared to traditional methods that do. It is robust to contrast changes and performs well across a wide range of image contrasts.